Hyperthermia induced by gold nanoparticles and visible light photothermy combined with chemotherapy to tackle doxorubicin sensitive and resistant colorectal tumor 3D spheroids - Roma-Rodrigues, Catarina (2020)
UIDB/04378/2020 SFRH/BPD/124612/2016